The Development of Independence Character Values in Ki Hajar Dewantara State Kindergarten - Aulia Rivanya Manoppo, Nur; Irma Septiani T. Dadi, Ade; Ain Dolongseda, Nur; Adrianto, Moh.; S. Kadir, Yani (Educationist: Journal of Educational and Cultural Studies, 2022)
Early childhood will go through the stages of psychosocial development proposed by Erikson, namely autonomy versus shame and doubt, where at this stage children must be given trust in order to develop their independence. Cultivating independence from an early age is very necessary. Independence will support children in learning to understand choices of behavior with risks that must be accounted for by children. The more restrained it is, the more difficult it will be for children to control their emotions, with the possibility that the behavior that will appear is rebellious behavior or even very dependent on others.